Halal blockchain: Bibliometric analysis for mapping research - Yanti, Roaida; Febrianti, Melinska Ayu; Qurtubi; Sulistio, Joko (Faculty of Business & Economics, Universitas Islam Indonesia, 2022)
Purpose – The main purpose of this study is to identify patterns and directions of halal blockchain research and find out the development of halal blockchain research trends.Methodology – This study used data from various articles in the Google Scholar database with the publication year limited from 2011 to 2022. Data collection used Harzing's Publish or Perish software. There were 353 articles that matched the keyword and they were processed by bibliometric analysis. Findings – This study found the basic pattern in halal blockchain research, trends in halal blockchain research, the relationship among research, research gaps, researchers who research a lot on halal Blockchain and the most published publications.Implications – This study contributes an overview of bibliometric studies in the halal blockchain literature, which can widen the previous literature and show more focused study topics by examining the abstracts and content of published articles. Findings related to evaluative and relational techniques can be helpful information for researchers, especially those new to this field of study. This bibliometric approach can be invaluable, especially for graduate students in supply chain management, logistics management, and industrial engineering.Originality – The originality offered by this research is to process research documents based on halal blockchain journals on Google Scholar. Thus, a lot of information and knowledge about halal Blockchain over the last 10th years can be useful for further research.